The effects of the cooperating teacher, knowledge of assessment procedures and use of feedback devices on the teaching performance of the teacher trainee - Waterman, Millicent A. (1978)
This study constructed a model for the supervision of teacher trainees in the In-Service Teacher Training Programme (ITTP), which consisted of three components: 1) the use of the cooperating teacher, 2) a knowledge of assessment procedures, and 3) the use of feedback devices. An experiment implementing the model was conducted for eight weeks with 32 teacher trainees from the Georgetown Centre of the ITTP, who were randomly assigned to eight treatment groups. Training packages were constructed and used to: (a) orient the cooperating teachers to their new role in supervising classroom practices of teacher trainees, (b) provide teacher trainees with a knowledge of how teacher performance was to be assessed, and (c) instruct teacher trainees in the use of feedback devices. The results of the data analysis indicated that the use of the cooperating teacher had a significant effect on teacher performance as measured by student achievement, but had minimal effect on all other criteria of teacher performance. A knowledge of assessment procedures had a negligible effect on all measures of teacher performance. The use of feedback devices had a significant effect on teacher performance as measured by student achievement, but was not significant for other measures of teacher performance. The interaction effect of a knowledge of assessment procedures and the use of feedback devices had a significant effect on teacher performance as measured by student achievement, but was not significant for other measures of teacher performance. The combined interaction effect of the cooperating teacher, a knowledge of assessment procedures, and the use of feedback devices was not significant, but tended to help teacher trainees to score highly. In three out of four concepts, teacher trainees who were supervised by cooperating teachers had the highest attitude profiles. It was concluded that the model was effective in part
Keywords: Educational models